Long-term effects of straw and straw-derived biochar on soil aggregation and fungal community in a rice–wheat rotation system - Naling Bai; Hanlin Zhang; Shuangxi Li; Xianqing Zheng; Juanqin Zhang; Haiyun Zhang; Sheng Zhou; Huifeng Sun; Weiguang Lv (PeerJ, 2019)
Background Soil aggregation is fundamental for soil functioning and agricultural productivity. Aggregate formation depends on microbial activity influencing the production of exudates and hyphae, which in turn act as binding materials. Fungi are also important for improving soil quality and promoting plant growth in a symbiotic manner. There is a scarcity of findings comparing the long-term impacts of different yearly double-crop straw return modes (e.g., straw return to the field and straw-derived biochar return to the field) on soil aggregation and fungal community structure in rice–wheat rotation systems. Methods The effects of 6-year continuous straw and straw-derived biochar amendment on soil physicochemical properties and the fungal community were evaluated in an intensively managed crop rotation system (rice–wheat). Soil samples of different aggregates (macroaggregates, microaggregates, and silt clay) from four different fertilization regimes (control, CK; traditional inorganic fertilization, CF; straw returned to field, CS; straw-derived biochar addition, CB) were obtained, and Illumina MiSeq sequencing analysis of the fungal internal transcribed spacer gene was performed. Results Compared to CF, CS and CB enhanced soil organic carbon, total nitrogen, and aggregation in 0–20 and 20–40 cm soil, with CB exhibiting a stronger effect. Additionally, agrowaste addition increased the mean weight diameter and the geometric diameter and decreased the fractal dimension (p < 0.05). Principal coordinates analysis indicated that fertilization management affected fungal community structure and aggregation distribution. In addition, CS increased fungal community richness and diversity, compared to CK, CB decreased these aspects. Ascomycota, unclassified_k_Fungi, and Basidiomycota were the dominant phyla in all soil samples. At the genus level, CB clearly increased fungi decomposing biosolids (Articulospora in macroaggregates in 0–20 cm soil and Neurospora in macroaggregates in 20–40 cm soil); decreased pathogenic fungi (Monographella in macroaggregates and Gibberella in microaggregates in 0–20 cm soil) and CO2-emission-related fungi (Pyrenochaetopsis in microaggregates and silt clay in 0–40 cm soil) (p < 0.05). Straw and biochar with inorganic fertilizer counteracted some of the adverse effects of the inorganic fertilizer with biochar showing better effects than straw.